Analisis Cyber Fraud Pada Platform Jual Beli Game Online: Studi Kasus Pada Platform Steam - Yarfa Dzardi (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to examine the reasons why people become victims of internet fraud through the Steam game trading platform and to discuss the modes used by the perpetrators. The three main informants of this research are victims of online fraud through the Steam game trading platform. Apart from that, it also seeks the opinions of experts about this case of online fraud. These results are expected to be able to provide deeper insights into cybercrime cases on the Steam platform and the strategies used by online fraudsters when using the Steam platform. In addition, the results are also expected to raise government awareness to take better measures to combat online fraud in the future. In addition, this research can serve as a basis for creating policies that protect the public from the threat of online fraud.